ECONOMIC FEASIBILITY STUDY OF BLACKSTONE COFFEE - Al Farisy, Haidar; Sukarno, Subiakto (Journal of Business and Management, 2017)
Abstract. The growth of coffee industry in the world keeps increasing. Coffee is constantly changing from a daily morning routine to a part of modern lifestyle. This phenomenon gives a huge possibility for coffee shop owners to draw their market. PT Blackstone is a new start-up company that founded recently in Indonesia that wants to enter coffee business. Based in Jakarta, Blackstone plans to invest in a new coffee shop business. The author intends to conduct a feasibility study to assess the investment in coffee shop business for PT Blackstone. The feasibility study uses financial tools such as profitability to determine profit margins, net present value (NPV) to consider the time value of money, internal rate of return (IRR) to calculate the discount rate of an investment, and lastly the payback period to evaluate proposed investment in how long it gets the return of the capital. After collecting the data, the author will process the data to extract the information needed for analysis which is the next step. The result of this economic feasibility study for PT Blackstone is feasible despite the profitability index that indicates no profitability. There are some suggestions for PT Blackstone to adjust this feasibility study result.Keywords: Coffee Shop, Feasibility Study, IRR, NPV, Payback Period, Profitability Index